Strategi Komunikasi Tim Produksi Dalam Mengemas Program Bincang Lifestyle di TVRI Sumatera Selatan - Emi Juniarti; Sepriadi Saputra; Rina Pebriana (PT. Pustaka Cendekia Publisher, 2025)
Effectiveness of the production team's communication strategy in packaging the show to be interesting and quality. This research aims to analyze the communication strategy of the production team in the Bincang Lifestyle program at TVRI South Sumatra using the POAC (Planning, Organizing, Actuating, Controlling) approach and Middleton's theory (1980). The research method used is descriptive qualitative, with data collection techniques through in-depth interviews, observation, and documentation.The results showed that in the planning stage, the production team conceptualized the event, determined the theme, and selected the speakers through internal meetings. However, the lack of involvement of the technical team from the beginning and the delay of the resource persons often become obstacles in the implementation. At the organizing stage, the work structure was clearly defined, but flexibility in the rotation of technical crew and duplicate tasks within the production team still created obstacles in coordination. Production implementation relied on verbal and non-verbal communication through handy talkies and WhatsApp to ensure smooth broadcast, but technical problems and sudden rundown changes were still common. Post-production supervision has not been optimal as evaluations are often conducted informally and are not well documented. Audience response monitoring is only done through YouTube viewership and annual surveys, with no in-depth analysis of the effectiveness of the communication strategies implemented. Overall, the communication strategy in the production of Bincang Lifestyle has worked quite well, but still needs improvement in coordination between team members, involvement of the technical team from the planning stage, and a more structured evaluation system. A more effective communication strategy is expected to improve the quality of the show and the program's appeal to viewers.